Inquiry Learning for Our Students and Our Future - Stephen P Gordon (Educational Considerations, 2025)
Society is currently experiencing a wave of misinformation and disinformation spread through social media and other means. Widespread false information threatens our social relationships and our democracy. A shift toward inquiry learning in PreK-12 education can both improve student learning in general and teach students to assess the validity of sources, assumptions, and assertions they encounter. Students who participate in inquiry learning explore real-world problems, practice critical thinking, and develop practical solutions. Inquiry learning also prepares students for democratic citizenship. Given the conventionality of many public school systems and outside political forces that might resist inquiry learning, the author suggests a developmental approach to implementing inquiry learning in schools where it is not currently emphasized. A developmental approach can be taken relative to learning level, curriculum level, and learning locale. Examples of inquiry learning in each of these three areas are provided. The author also suggests future research on the long-term effects of inquiry learning in PreK-12 education on graduates’ lives beyond school.
Keywords: Inquiry learning; learning levels; curriculum levels; learning locales